Sports culture and its relationship to some basic skills of the rope routine in rhythmic gymnastics for third-stage female students - Jasem, Zeena (Journal of Physical Education, 2025)
The sports culture has an influential and effective role in spreading and consolidating the principles of sports spirit among female students on the one hand, as well as spreading awareness and blocking unwanted behavior and emphasizing their psychological and social compatibility on the other hand. The research problem lies in the researcher’s observation of the lack of interest of students in sports culture in addition to sports and their relationship to the performance of certain skills. The basics of rope routine in rhythmic gymnastics Objectives of the research: to prepare a sports culture scale for third-stage female students at the Faculty of Physical Education and Sports Sciences, University of Baghdad, and to know some basic skills of the rope routine in rhythmic gymnastics. Knowledge of the relationship between sports culture and some basic skills of the rope tool in rhythmic gymnastics for third-stage students at the College of Physical Education and Sports Sciences, University of Baghdad. In order to determine the objectives of the research, the researcher used the descriptive method using the survey method. The research sample was selected from all the students of the third stage of the society for the research necessities and divided into the following: (10) a student for the survey sample and (80) for the construction and application sample. (26) The researcher prepared the Sports Culture Scale, using several statistical procedures as well as measuring some rope skills, then used several statistical means to obtain the results, through which she concluded the sample was distinguished by sports culture through the results of the scale. Students of the third stage at the College of Physical Education and Sports Sciences, University of Baghdad, have an average performance of some rope skills. Sports culture plays a positive role in the performance of some rope skills in rhythmic gymnastics. They also recommended that the scale should be adopted for third-stage students as well as other stages. Continue to encourage students to exchange knowledge among themselves, especially those that are new